2019
DOI: 10.1136/bmjopen-2018-028119
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities for young people with cancer: a UK priority setting partnership with the James Lind Alliance

Abstract: ObjectivesTo conduct a UK-wide survey of young people who have experienced cancer, carers and professionals, to identify and prioritise research questions to inform decisions of research funders and support the case for research with this unique cancer population.DesignJames Lind Alliance Priority Setting Partnership.SettingUK health service and community.MethodsA steering group oversaw the initiative and partner organisations were recruited. Unanswered questions were collected in an online survey. Evidence se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 18 publications
2
72
0
Order By: Relevance
“…This may have influenced which questions made it to the Top 10. This is a typical tendency in survey research and was also observed in other PSPs [ 20 ]. Future PSPs may want to come up with and employ alternative strategies to ensure equal representation of all members of society.…”
Section: Discussionsupporting
confidence: 76%
“…This may have influenced which questions made it to the Top 10. This is a typical tendency in survey research and was also observed in other PSPs [ 20 ]. Future PSPs may want to come up with and employ alternative strategies to ensure equal representation of all members of society.…”
Section: Discussionsupporting
confidence: 76%
“…This may have in uenced which questions made it to the Top 10. This is a typical tendency in survey research and was also observed in other PSPs (20). Future PSPs may want to come up with and employ alternative strategies to ensure equal representation of all members of society.…”
Section: Discussionmentioning
confidence: 69%
“…Consequently, different individual-level or environmental-level factors will contribute to one’s psychological adaptation and recovery. As psychosocial well-being remains an unmet need and among the most important topics for AYAs with cancer, 26 we have to develop a better understanding of how different subgroups of patients, though afflicted with the same diagnosis, respond differently based on their individual biopsychosocial profile.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, national as well as international initiatives have recognised the importance of psychosocial impact of cancer diagnosis in youth and are calling for research initiatives that investigate psychopathology and promote psychological well-being in young patients. 26 27 However, the field lacks a common definition of resilience 28 and still relies on latent models of assessing mental health (ie, having depression leads to fatigue and/or loss of interest). 29 …”
Section: Introductionmentioning
confidence: 99%